Facile fabrication of CuO/Ag2Se nanosized composite via hydrothermal approach for the electrochemical energy conversion system. (1st December 2022) - Abdullah, Muhammad; John, Peter; Manzoor, Sumaira; Ghouri, Muhammad Ishfaq; Hegazy, H.H.; Chugtai, Adeel Hussain; Aman, Salma; Shawky, Ahmed M.; Ashiq, Muhammad Naeem; Taha, T.A.
Abstract: The composite electrodes are sustainable way of generating high-performance supercapacitor materials, and are easily synthesized via cost effective methods. Here, we state the synthesis of CuO, Ag2 Se, CuO/Ag2 Se (COAS) nanocomposites via a hydrothermal method specifically for energy conversion devices. The structural, morphological and textural properties of fabricated material are evaluated with scanning electron microscopy (SEM), x-ray diffraction (XRD), Brunauer Teller Emmett analyses (BET). The electrochemical efficiency of the generated materials is further determined using galvanostatic charge discharge (GCD), electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), electrochemical active surface area (ECSA), electrochemical impedance spectroscopy (EIS), and chronoamperometry (CA) using Ni foam as conductive substrate under 2.0 M KOH electrolyte. Electrochemical results revealed about CuO/Ag2 Se heterostructure displays specific capacitance (Cs) of 1543.42 F g −1 at 1 A g −1 . COAS electrode has higher cycle stability, along with the capacitance of 97 % retained up to 2000 cycles at 1.5 A g −1 . In addition, COAS pseudocapacitor exhibited an energy density (Ed ) of 34.81 Wh Kg −1 and a power density (Pd ) of 201.5 W Kg −1 . This study not only highlighted huge potential related to electrode material CuO/Ag2 Se, as well as revolutionary approach for manufacturing affordable, multi element composite materials with high performance that may be applicable in an inclusive variety of applications in future era. Highlights: A facile hydrothermal route is employed for the fabrication of CuO/Ag2 Se (COAS) nanocomposite for energy storage devices. The COAS exhibited the symmetrical shaped nanoparticle decorated on the surface on the nanorods. COAS nanocomposite displays 1401 F g −1 specific capacitance at a current density of 1.5 A g −1 . The fabricated material showed high stability over 35 h.